PENGEMBANGAN MEDIA CORONG BERHITUNG DALAM MENERAPKAN ABSTRAKSI KONSEP DASAR MATEMATIKA DI MIN 1 SLEMAN YOGYAKARTA - Rahmawati, Ely; Wulandari, Yeni (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2020)
This research is motivated by the problem of Mathematics in Elementary Schools or Madrasah Ibtidaiyah (MI). In practice, learning begins with an explanation of concepts accompanied by examples, followed by practical questions. This learning approach tends to only practice basic mathematical skills in a limited and isolated manner and the questions presented are not relevant in student’s daily lives, so learning is less meaningful. It was discovered in MIN 1 Sleman that grade II students had difficulty understanding subtraction material and roman numerals from the basic concepts of mathematics. Therefore, from the problems in the field the researchers are trying to develop numeracy flearning media that applies abstracts in learning. development of mathematics learning tools for grade II calculation funnels to form the basic concepts of mathematical abstraction thinking is done using 7 steps or a Research and Development method by Borg & Gall. The quality of learning device products developed through a series of validity tests by validator experts, teachers, and peers continued with limited trials including tests of learning performance, student responses, and trialling the learning outcomes of excellent category scores, so that the learning tools developed were feasible to use.